Aerofoil trailing‐edge noise prediction models for wind turbine applications. Issue 10 (19th May 2017) - Lau, Alex Siu Hong; Kim, Jae Wook; Hurault, Jeremy; Vronsky, Tomas; Joseph, Phillip
Abstract: This paper proposes a modified TNO model for the prediction of aerofoil trailing‐edge noise for wind turbine applications. The capabilities of the current modified model and four variants of the TNO model are analysed through a comprehensive study which includes 10 aerofoils and involves two different wind tunnels. The Reynolds numbers considered are between 1.13 and 3.41 million, and the effective angles of attack are between −2.20° and 13.58°. The merit of a model is assessed by comparing two aspects of the numerically predicted and the experimentally measured sound pressure level spectra: the sound pressure level difference between two different aerofoils at similar lift coefficients within a certain frequency range (referred to as the delta noise); and the closeness in terms of spectral magnitude and shape of the predicted and measured sound pressure level spectra. The current modified model is developed by deriving new formulations for the computation of the wall pressure fluctuation spectrum. This is achieved by using the approximate ratio of the normal Reynolds stress components for an anisotropic flow over a flat plate to estimate the vertical Reynolds stress component, and by introducing new stretching factors to take the effects of turbulent flow anisotropy into account. Compared with the four TNO model variants tested, the current modified model has strong delta noise prediction ability, and is able to predict sound pressure level spectra that are more consistent and closer to measurements for the vast majority of aerofoils and flow conditions tested in the two wind tunnels. Copyright © 2017 John Wiley & Sons, Ltd.